The Damaged Bone and the Lone Mushroom : Þórr’s Goats, Tyrolean Chamois, Sami Bears and Canadian Salmon - Bek-Pedersen, Karen (Religionsvidenskabeligt Tidsskrift, 2022)
ABSTRACT: The article carries out a comparative exercise focusing on the Norse myth about Þórr slaughtering and then reviving his goats. It has sometimes been argued that the myth is a borrowing from a Christian legend about Saint Germanus. This is, however, problematic since similar traditions are found in Alpine, Caucasian, Sámi and even Native American contexts, in all cases with a non-Christian flavour. The article concentrates on those analogues that are closest to the Norse myth in terms of the central details and considers what might lie behind this seemingly odd distribution. The suggestion is that the central motif constitutes a shared tradition across the northern hemisphere that has its roots in the very deep layers of human history. RESUME: Artiklen præsenterer en komparativ øvelse med fokus på den norrøne myte om Thor, der slagter sine geder og derpå vækker dem til live igen. Den teori er flere gange blevet fremsat, at myten er lånt fra en kristen helgenlegende om Sankt Germanus. Dette er imidlertid problematisk, idet lignende traditioner findes i Alperne, Kaukasus, Sápmi og endda indfødte canadiske kulturer, i alle tilfælde uden kristen forklædning. Artiklen fokuserer på de parallelle fortællinger, som følger den norrøne myte tættest med hensyn til de centrale detaljer, og overvejer, hvad der kan ligge til grund for denne løjerlige spredning. Forslaget er, at det centrale motiv udgør en fælles tradition på tværs af den nordlige halvkugle med rødder i den meget dybe historie.